Study on true triaxial compression test of columnar jointed rock mass made of 3D printed polymer and cement-based materials - Zhenbo Xu; Zhende Zhu; Xiaoyu Wang; Xinghua Xie; Chao Jiang (Case Studies in Construction Materials)
In this study, a series of true triaxial compression tests were carried out to systematically analyze the mechanical response, failure mode and energy evolution process of irregular columnar jointed rock mass under different irregularity, dip angle and intermediate principal stress ratio ( σ2 / σ3). In this paper, the ' complex stress ' condition is defined as the true triaxial stress state of σ1 ≠ σ2 ≠ σ3, and the nonlinear mechanical behavior and failure mechanism of rock mass under this stress state are mainly revealed. The results show that the dip angle and intermediate principal stress ratio are the main factors affecting the mechanical properties and failure modes of columnar jointed rock mass. The change of dip angle leads to the ' U ' -shaped change trend of rock mass strength and shows significant mechanical anisotropy. The increase of the intermediate principal stress ratio strengthens the process of crack propagation and energy dissipation, which significantly affects the transformation of failure modes. Irregularity mainly affects the plastic deformation process, and the effect on strength is relatively small. In terms of energy evolution, it is found that the energy input, transformation and dissipation process of columnar jointed rock mass has obvious stage and nonlinear characteristics, especially in the plastic stage, energy dissipation is dominant and closely related to the failure mode. In addition, based on the traditional Hoek-Brown strength criterion, this paper introduces the irregular joint factor and proposes an improved strength prediction model.